HUBUNGAN PENGGUNAAN ALAT KONTRASESPSI HORMONAL Depo Medroxy Progesterone Acetate (DMPA) TERHADAP CITRA TUBUH PADA WANITA USIA SUBUR DI KECAMATAN JATIUWUNG - Peni Krisdianti Pambayun (Nusantara Hasana Journal, 2022)
The wage of contraception 3 months DMPA (Depo Medroxy Progesteron Acetat) have mayor side effect, there is weight change. Acceptor KB, DMPA injection was experience weight changed influenced by progesterone hormone, so that stimulated appatice hormone in hypothalamus.  The purpose of the reseach there was to analyzed differential weight before and after used injection contraception DMPA in Kecamatan Jatiuwung Tangerang Banten. This reseach used analytical comparation with cross sectional, sampling Total sampel of this research is 75. This research used consecutive sampling. Data was analyzed by chi – square test. There was difrential weight before and after used injection contraception (p-value = 0,03). From this reseach there was diffrential weight before and after used injection contraception DMPA. KB Acceptor can be expected to utilized facility and infrastructure form heather to reduce mortality and give space baby births with inaection KB without over worries with side effect from KB contraception like injection KB.